Industrial training report: Jabatan Kehakiman Syariah Negeri Kelantan Kompleks Kehakiman Syariah Negeri Kelantan / Nurul Ashikin Senik - Senik, Nurul Ashikin (Perpustakaan Tengku Anis, 2017)
The industrial training report based on the period from 2nd February 2017 until 3th June 2017 in Upstream Information Management and Information Technology department at Kelantan Syariah Judicial Department. In this industrial training report the student will be discussing regarding the period starting with the organization introductory followed with department introduction along business tasks. In this report it was highlighted about the training activities, experiences skills and challenges that the student has been encountered. All training activities and special project are recorded in this industrial training report. The student has been involved in creating corporate branding which demanding the ability of the student to create powerful and impactful corporate branding.